1999
DOI: 10.1002/(sici)1521-186x(1999)20:1<48::aid-bem7>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical progression of transplanted large granular lymphocytic leukemia in Fischer 344 rats exposed to 60 Hz magnetic fields

Abstract: The purpose of this study was to determine if 60 Hz magnetic fields can alter the clinical progression of leukemia in an animal model. Large granular lymphocytic (LGL) leukemia cells from spleens of leukemic rats were transplanted into young male Fischer 344 rats, producing signs of leukemia in approximately 2–3 months. The animals were randomly assigned to 4 treatment groups (108/group) as follows: 1) 10 G (1.0 mT) linearly polarized 60 Hz magnetic fields, 2) sham exposed [null energized unit with residual 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…As discussed above, since our review was published these experiments have been completed. Some of the results have been published in peer-reviewed format (81,82), and the complete study results are available in report form (79,80,101). These experiments were all conducted according to GLP, and their progress was periodically reviewed by an independent auditor.…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…As discussed above, since our review was published these experiments have been completed. Some of the results have been published in peer-reviewed format (81,82), and the complete study results are available in report form (79,80,101). These experiments were all conducted according to GLP, and their progress was periodically reviewed by an independent auditor.…”
Section: Resultsmentioning
confidence: 76%
“…In our previous review (1) we discussed experiments of Dieter and colleagues (100) and suggested that their report of enhancement effects may not be definitive. More (79)(80)(81)(82)101) appear to be well done, the significance of the results with respect to whether MFs have any leukemogenic potential is uncertain. Below, we review the experiments conducted by this group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations